"Czuję, więc jestem", czyli o uniwersum emocji - Tichoniuk-Wawrowicz, Ewa; Karczewska, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article aims to present the richness of the world of affects in the sense of emotional states. They are our adaptive heritage and are key functions of the brain that allow us to assess and hierarchise stimuli coming from the environment and our bodies, which makes them become an important factor in the functioning of individuals and communities. This paper is, at the same time, an introduction to the monograph "W uniwersum emocji: literatura, nauka, sztuka" ("In the universe of emotions: literature, science, art.").
Keywords: afekt; emocje; jednostka; społeczność; dziedzictwo; affect; emotions; individual; community; heritage